Factors Influencing the Use of Internet Resources by Pre-Clinical Medical Students in Selected Universities in Edo and Anambra States, Nigeria - Obinyan, Oluwatoyin Oyeyemi (MiddleBelt Journal of Library and Information Science, 2020)
There has been paucity of current reading materials in print for pre-clinical medial students due mainly to high cost of procurement. To savage and remedy the situation, institutions are subscribing to Internet resources. Even at this, there is a gnawing perceived low use of Internet resources among the students in the selected universities, hence, this study is undertaken to explore the factors influencing the use of Internet resources by pre-clinical medical students in universities in selected States in Nigeria. The study population comprised the pre-clinical medical students in the selected states. Total enumeration of the population was adopted. Data were collected using questionnaire, out of the 949 copies administered, 704 were found usable given a response rate of 74.2%. Data were analysed using frequency count, mean and standard deviation. The study revealed that majority of the students ( X = 3.0) used Medline, Online reference materials and E-mail. Other Internet resources that were significantly used were HINARI ( X =2.7), Pubmed and e-journals ( X = 2.6). Most of the students use Internet resources for academic purposes ( X = 3.0), while only a few ( X = 2.1), used Internet resources for entertainment purposes, they use Internet resources in cybercafé ( X = 3.0), and at home/hostel ( X = 2.7). The constraints mentioned include low speed of connection, electricity failure, lack of awareness and language of the contents. The study, therefore, recommended among others that use of Internet resources should be included as a formal course in medical education programme of the students.